Application of supported ionic liquid phase catalyst systems in the hydroformylation of olefin-containing mixtures to aldehyde mixtures with high portion of nonbranched aldehydes. - Franke, Robert; Brausch, Nicole; Fridag, Dirk; Christiansen, Andrea; Becker, Marc; Wasserscheid, Peter; Haumann, Marco; Jakuttis, Michael; Werner, Sebastian; Schönweiz, Andreas (2012)
The subject of the present invention is a catalyst with increased durability based on compn. of (a) an inert, porous substrate, (b) an ionic liq., (c) Rh, (d) a phosphorus-contg. org. ligand, (e) at least an org. amine. A further the subject of the present invention is a procedure for the hydroformylation of olefin-contg. hydrocarbon mixts. to aldehyde mixts. whereby: (a) the water content of the olefin-contg. hydrocarbon mixt. is adjusted to ≤20 ppm, (b) the content of multifunctional unsatd. compds. in the olefin-contg. hydrocarbon mixt. is adjusted continually to ≤3000 ppm, (c) the mol. ratio of org. amines to phosphorus-contg. ligands is ≥4:1; and (d) the mol. ratio of phosphorus-contg. org. ligand to Rh is ≥10:1. A typical catalyst consists of silica support, rhodium acetylacetonate dicarbonyl, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, 6,6'-[[3,3'-di-tert-butyl-5,5'-dimethoxy[1,1'-biphenyl]-2,2'-diyl]bis(oxy)]bis[dibenzo[d,f][1,3,2]dioxaphosphepin] and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and a typical reaction feed contains 1-butene, isobutene, cis-2-butene, trans-2-butene, n-butane, and isobutane, with the product being n-pentanal. [on SciFinder(R)]
Keywords: ionic liq rhodium phosphorus ligand amine catalyst supported hydroformylation; tertiary butyldimethoxy biphenyldiylbisoxybis dibenzodioxaphosphepin catalyst hydroformylation butene pentanal manuf; hydroformylation olefin catalyst unbranched aldehyde manuf; butene hydroformylation pentanal manuf catalyst; silica support hydroformylation catalyst butene pentanal manuf; rhodium acetylacetonatedicarbonyl catalyst hydroformylation butene pentanal manuf; ethylmethylimidazolium fluoromethanesulfonylimide catalyst hydroformylation butene pentanal manuf

Continuous Gas-Phase Hydroformylation of a Highly Diluted Technical C4 Feed using Supported Ionic Liquid Phase Catalysts - Haumann, Marco; Jakuttis, Michael; Franke, Robert; Schönweiz, Andreas; Wasserscheid, Peter (ChemCatChem, 2011)
The concept of supported ionic liquid phase (SILP) catalysis has been established in recent years by our group and others. Its application in continuous catalytic gas-phase processes provides a very attractive way to bridge the gap between homogeneous and heterogeneous catalysis. In this contribution, we extend SILP hydroformylation catalysis to reactions with a highly diluted, technical C4 feed containing 1.5 % 1-butene, 28.5 % 2-butenes, and 70 % of inert n-butane. To obtain the desired product, n-pentanal, the Rh-biphephos catalyst system was immobilized in the SILP system to allow for consecutive isomerization/hydroformylation activity. The resulting SILP catalyst material converted up to 81 % of the reactive butenes, with a residence time of 155s in the reactor. An n-pentanal selectivity greater than 92% was realized for more than 500h time-on-stream in the continuous gas-phase reaction. Post-reaction NMR studies revealed no significant loss of the phosphite ligand through ligand oxidation during the reaction.

Immobilized catalytically active composition for hydroformylation of olefin-containing mixtures. - Dyballa, Katrin M.; Franke, Robert; Hahn, Hanna; Becker, Marc; Schönweiz, Andreas; Debuschewitz, Jonas; Walter, Simon; Woelfel, Rene; Haumann, Marco; Wasserscheid, Peter; Kaftan, Andre; Laurin, Mathias; et al. (2014)
Compn. used as a catalyst for hydroformylation of olefinically unsatd. hydrocarbon mixts. comprises a metal complex, esp. an Rh complex having a phosphine or phosphite ligand, on an inert porous carrier, and is loaded for the purposes of the hydroformylation with the aldol byproduct of the desired aldehyde, in the manner of an application of the "Supported Liq. Phase" (SLP) concept. Thus, aldol ( 2-Methylpent-2-enal) doping leads to increasing yield of propanal as a product of hydroformylation of ethylene with H2 and CO on a solid catalyst consisting of acetylacetonatodicarbonylrhodium supported on Trisopor 423. [on SciFinder(R)]
Keywords: immobilized hydroformylation catalyst olefin aldehyde

Ligand-Modified Rhodium Catalysts on Porous Silica in the Continuous Gas-Phase Hydroformylation of Short-Chain Alkenes-Catalytic Reaction in Liquid-Supported Aldol Products - Schönweiz, Andreas; Debuschewitz, Jonas; Walter, Simon; Woelfel, Rene; Hahn, Hanna; Dyballa, Katrin M.; Franke, Robert; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2013)
Ligand-modified Rh complexes were physically adsorbed on the surface of porous silica. The resulting materials were subjected to the continuous gas-phase hydroformylation of C-2 and C-4 alkenes. The ligands used for catalyst modification were bidentate phosphorus ligands known from the literature, namely, sulfoxantphos (1) and a benzopinacol-based bulky diphosphite 2. The tested catalyst materials were active and, in particular, selective as in comparable homogeneous liquid-phase experiments. Long-term stability experiments over 1000h on stream showed minor deactivation. A significant increase in the catalyst mass after the reaction was detected by weighing and thermogravimetric analysis. By using headspace-GC-MS, the mass increase could be attributed to high-boiling compounds, which are formed insitu during the catalytic reaction itself and accumulate inside the pores of the support. Evidence is given that the initially physisorbed catalyst complexes dissolve in the high-boiling aldol side-products, which are suitable solvents for the active catalyst species and provide a liquid-phase environment held by capillary forces on the support.
Keywords: aldol reaction; hydroformylation; immobilization; rhodium; supported liquid

Rhodium-Phosphite SILP Catalysis for the Highly Selective Hydroformylation of Mixed C4 Feedstocks - Jakuttis, Michael; Schönweiz, Andreas; Werner, Sebastian; Franke, Robert; Wiese, Klaus-Diether; Haumann, Marco; Wasserscheid, Peter (Angewandte Chemie International Edition, 2011)
The cat. that got the butene: Highly active and selective diphosphite ligands are applied for rhodium-catalyzed supported ionic liquid phase (SILP) hydroformylation and make it possible to form linear n-pentanal with exceptional selectivity from a mixed butene feedstock by combined isomerization and hydroformylation (see picture, vials 1–4 show typical SILP catalysts employed in this study.). The SILP catalyst is stable for more than 800h on stream.

Selectivity enhancement in the catalytic hydrogenation of propionitrile using ionic liquid multiphase reaction systems - Obert, Katharina; Roth, Daniel; Ehrig, Martin; Schönweiz, Andreas; Assenbaum, Daniel; Lange, Harald; Wasserscheid, Peter (Applied Catalysis A-General, 2009)
A new ionic liquid based, multiphase reaction system was investigated for the catalytic hydrogenation of propionitrile. The reaction system under investigation consisted of a solid heterogeneous Ru-catalyst (Ru on carbon), two liquid phases and the hydrogen gas-phase. By using two liquid phases in the reactor – of which one was an ionic liquid – it was possible to improve significantly the selectivity for the formation of propylamine by suppressing consecutive reactions to dipropylamine and tripropylamine. This enhanced selectivity resulted either from the protonation of the primary formed amine (in case of the Brønsted acidic ionic liquids dimethylcyclohexylammonium hydrogensulfate and 1-butylimidazolium hydrogensulfate) or from the extraction of the primary amine into the organic phase (in case of a 1-ethyl-3-methylimidazolium ethylsulfate/1,2,4-trichlorobenzene biphasic system).

Supported homogeneous catalyst makes its own liquid phase - Kaftan, Andre; Schönweiz, Andreas; Nikiforidis, Ioannis; Hieringer, Wolfgang; Dyballa, Katrin M.; Franke, Robert; Görling, Andreas; Libuda, Jörg; Wasserscheid, Peter; Laurin, Mathias; Haumann, Marco (Journal of Catalysis, 2015)
2,2'-((3,3'-di-tert-butyl-5,5'-dimethoxy-[1,1'-biphenylj-2,2'-diyl)-bis(oxy))bis(4,4,5,5-tetraphenyl-1,3,2-dioxaphospholane) modified rhodium complexes molecularly adsorbed onto porous silica powder show surprisingly high activity and regioselectivity in the gas-phase hydroformylation of propene to but-anal, with no sign of deactivation. Operando IR investigations combined with density functional theory calculations confirm a side reaction: the aldol condensation of the butanal products. These heavier by-products accumulate inside the pores of the catalytic material. IR and gas chromatography show a direct relation between formation of enones, products of the aldol condensation, performance, and stability of the catalytic system. This demonstrates that the aldol condensation products generated in situ act as a solvent providing an ideal environment to the impregnated homogeneous catalyst. (c) 2014 Elsevier Inc. All rights reserved.
Keywords: Hydroformylation; Supported homogeneous catalysis; Operando spectroscopy; Infrared spectroscopy; Density functional theory; Silicon dioxide; Rhodium

Tuning catalyst performance in the SILP-catalyzed gas-phase hydroformylation of but-1-ene by choice of the ionic liquid - Schörner, Markus; Schönweiz, Andreas; Vignesh, Stefanie; Mokrushina, Liudmila; Thommes, Matthias; Franke, Robert; Haumann, Marco (Journal of Ionic Liquids, 2023)
For the industrially relevant hydroformylation of but‑1-ene the concept of supported ionic liquid phase (SILP) has been applied previously. In this work, we have studied the influence of the type of ionic liquid (imidazolium and phosphonium based cations, various anions) on the solubility of the three reagents but‑1-ene, carbon monoxide and hydrogen. For the olefin, the predicted solubility values were determined using the COSMO-RS software tool. These data were compared to the experimentally determined values. A correlation between the predicted solubility and the observed activity within similar ILs could be observed. The highest activity could be obtained with the IL [N1888][NTf2]. A variation of the olefin chain length supported the observed correlation between solubility and activity. With increasing chain length, the activity of the SILP catalyst also increased. For the undesired consecutive reaction leading to aldols it was found that the substrate solubility does not significantly influence the activity or hydrocarbon accumulation under the used reaction conditions. The anion had a more pronounced effect on the accumulation of aldols, with hydrophilic Cl− and [EtOSO3]− showing lowest accumulation as well as aldol formation activity, while [NTf2]− showed highest values for both accumulation and formation activity. It was shown that the Kamlet-Taft-parameter β is a suitable value to be correlated with activity and accumulation for different ILs.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Aldol condensation; Hydroformylation; Kamlet-Taft-parameter; Rhodium; Solubility; Supported ionic liquid phase (SILP)